A Review on Effect of Cooling Method and Cutting Tool Geometries on Surface Defect of Carbon Fibre Reinforced Polymer Workpiece by End Milling Process - Leong, Chee Wai; Abd Rahim, Erween (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this modern industrial revolution era, the usage of advance material are very common. Carbon Fibre Reinforced Polymer (CFRP) is one of the common composite that has been used in the industries due to desired properties, such as high tensile strength to weight ratios, tensile modulus to weight ratios, low coefficient of thermal expansion, high fatigue strengths and thermal conductivity. However, the machining of CFRP is always a challenging task. A lot of studies have been conducted to improve the machinability of CFRP. In this study, we will be focusing on the effect of cooling condition and tools’ geometry on the surface defect of CFRP during milling. A review study on previous researches were done to gather informations for our study. From the study, we found out that cryogenic cooling method is the best for the milling of CFRP due to the lower temperature causing more resistance against delamination of CFRP. High value of rake angle, helix angle, and clearance angle will provide a better surface finish. However, the effect of clearance angle is not as significant as the effect of rake angle and helix angle on surface roughness.